Internet of Things: The Art of Embedding Intelligence Everywhere - Deshmukh, RJ; Kulkarni, AJ (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 3 No 2 (2019): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
In the course of the most recent decade Internet has made huge effect in our economies and social life by setting revolution in networking. The internet has been a noteworthy driver of worldwide data and media sharing. The Internet of Things portrays a worldwide neural system in cloud of intercommunicating gadgets in continuation with this pattern, it is ready to rise as a “Web of Things” where the web will give a mechanism for physical world to interact and create a benchmark in communication. With this the computerized data innovation can merge in the physical world to the online world to make it useful for appliances from smart homes to smart cities, security to wearable’s, agriculture to medical care, industrial automation to energy management.8 How to cite this article: Deshmuk RJ, Kulkarni AJ. Internet of Things: The Art of Embedding Intelligence Everywhere. J Adv Res Appl Arti Intel Neural Netw 2019; 2(2): 17-20.